1999
DOI: 10.1149/1.1391705
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical and Corrosion Properties of Fe2 O 3 ‐ TiO2 Artificial Passivation films

Abstract: In order to develop thin coating films having extremely high corrosion resistance, we have synthesized artificial passivation films which simulate the composition and the structure of passive films on stainless steels and valve metals by metallorganic chemical vapor deposition (MOCVD). According to our results, the double-oxide films such as 5 have sufficiently high corrosion resistance in strong acid solutions. Since most of these films have semiconducting nature, applications of these films as semiconductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In order to investigate whether there is a similar effect of the surface TiO 2 segregation on the Ti 4+ doped Fe 2 O 3 , we also compared the effect of surface treatment on the photoelectrochemical properties of pure and Ti 4+ doped Fe 2 O 3 samples. Since a pure Fe 2 O 3 sample was dissolved in acid solution more easily than a Ti 4+ doped Fe 2 O 3 sample, 32,33 pure Fe 2 O 3 was corroded for a shorter time (about ve minutes). A similar onset potential shi was observed on the pure Fe 2 O 3 electrode (see Fig.…”
Section: Effect Of Surface Corrosion On the Onset Potential Of A Fe 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate whether there is a similar effect of the surface TiO 2 segregation on the Ti 4+ doped Fe 2 O 3 , we also compared the effect of surface treatment on the photoelectrochemical properties of pure and Ti 4+ doped Fe 2 O 3 samples. Since a pure Fe 2 O 3 sample was dissolved in acid solution more easily than a Ti 4+ doped Fe 2 O 3 sample, 32,33 pure Fe 2 O 3 was corroded for a shorter time (about ve minutes). A similar onset potential shi was observed on the pure Fe 2 O 3 electrode (see Fig.…”
Section: Effect Of Surface Corrosion On the Onset Potential Of A Fe 2...mentioning
confidence: 99%
“…S1 †) due to its higher stability than pure Fe 2 O 3 . 32,33 In this study, we employed an acid solution to corrode the surface of Ti 4+ doped Fe 2 O 3 and found that the pretreated Ti 4+ doped Fe 2 O 3 sample exhibited a 100 mV cathodic shi of the photocurrent onset potential. The present hematite photoanodes showed a similar photocurrent onset potential to the lowest values obtained by using electrocatalysts and functional over-layers.…”
Section: Introductionmentioning
confidence: 99%
“…229 Similarly, a mixed Fe 2 O 3 -TiO 2 composite film exhibited enhanced corrosion resistance relative to a neat Fe 2 O 3 surface. 230 These mixed oxide films were prepared by a cold wall low-pressure MOCVD technique.…”
Section: Light Emission and Nanocrystal Size Monodispersitymentioning
confidence: 99%
“…It was found that TiO 2 thin film coatings, applied by a spray pyrolysis technique, cathodically photoprotected the steel surface from corrosion . Similarly, a mixed Fe 2 O 3 −TiO 2 composite film exhibited enhanced corrosion resistance relative to a neat Fe 2 O 3 surface . These mixed oxide films were prepared by a cold wall low-pressure MOCVD technique.…”
Section: Illustrative Examples Of Performance or Property Enhancement...mentioning
confidence: 99%
“…54) nearly coincident with the mobility gap, m g E , have been 2.95 137 2.80 a 0.15 Fe 0.1 Ti 0.9 O 1. 95 3.15 145 3.00 a 0.15 a Estimated from the corresponding crystalline phases according to Eqs. (60a) and (61).…”
Section: (Iii) Optical Gap In Amorphous Materialsmentioning
confidence: 99%